In Christian Humanism an Impossibility? - Gerard Saverimuttu, A. (University of jaffna, 2018)
This paper intends to examine the question of whether the notion of “ Christian Humanism” is sustainable as a valid term, or whether it is contradiction in terms, as some have claimed. Today the term “ humanism” seems almost to defy precise definition; for its meaning has been fluctuating over the centuries; and one finds different types of humanism: medieval humanism, or just plain Humanism. This has led to the debate: Is “Christian Humanism” itself a valid term? Those who would reply in the negative claim that true humanism denies the existence of any supernatural agency and bases its ethical values merely on human nature and not on the revelation of any God: therefore, they question how these tenets can be reconciled with the beliefs of Christianity. The 20th- century French philosopher Jacques Maritain, a staunch defender of the validity of the term “Christian humanism,” considered that the crisis of the Modern Era is centred on the question of what humanism is. The anthropo-centric humanisms of liberalism and communism of his time, Maritain reasoned, were anti-human because they refused to recognize the whole human person. If the spiritual dimension of human nature is discarded, there will be only a partial humanism, and not an integral humanism. Maritain defended a theo-centric humanism, which he named “ integral humanism,” and which views the individual human being as a unified whole (having both material and spiritual dimensions), while viewing human beings in society as partakers in a common good. This integral humanism aimed to make the individual human being more fully human in all respects, by bringing the material and the spiritual dimensions together without reducing the value of either. The present-day author jens Zimmermann, which defining humanism in line with Maritain’s integral humanism, proposes an ancient “incarnational humanism,” not as a new invention, but rather as a retrieval of an ancient Christian humanism, in response to the widespread desire of our times for a common humanity beyond religious and secular divisions. As early Church Fathers have pointed out. The Christian concept of the widespread desire of our time for a common humanity beyond religious and secular divisions. As early Church Fathers have pointed out, the Christian concept of the incarnation (or”enfleshment”) of the eternal Word of God in human flesh as Jesus Christ, gave rise to the notion of a common humanity: Christ had ”recapitulated humanity” by affirming and redeeming it through his incarnation, death and resurrection so that humanity would be reinstated to its ultimate purpose of union with God.
Keywords: Christian humanism; Contradiction; Jacques Maritain; Integral humanism; Theocentric humanism; Jens zimmermann; Incarnational humanism; Enfleshment; Recapitulation